Bone-derived vesicles and associated miRNAs as a multi-targeted strategy for bone regeneration - Maggio, Mimma (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2026)
Bone is a dynamic, mechanosensitive tissue that undergoes continuous remodelling through coordinated interactions between osteoblasts, osteoclasts, and osteocytes. Mechanical loading is a key regulator of this process, yet how mechanical cues are communicated between bone cells remains incompletely understood. This work investigates extracellular vesicles (EVs) as mediators of bone cell communication and explores mechanical stimulation as a strategy to optimise vesicle-based, cell-free approaches for skeletal regeneration. We demonstrate that EV-mediated regulation of osteoclastogenesis is cell-type specific and mechanically regulated, with EVs derived from mechanically stimulated osteocytes acting as potent inhibitors of osteoclast differentiation and activity. To address translational limitations in EV production, nanovibrational bioreactor stimulation was evaluated as a scalable strategy to enhance vesicle yield; although EV production increased, nanovibration did not induce a mechanically driven regenerative response. To overcome limitations associated with cell-derived vesicles, matrix vesicles isolated directly from mineralised bone were identified as a high-yield therapeutic source with multi-targeted regenerative effects, promoting osteogenesis and angiogenesis while suppressing osteoclastogenesis. Finally, mechanical loading was shown to shape EV microRNA cargo, identifying miR-150-5p as a mechanosensitive regulator with multi-targeted regenerative potential, linking mechanical cues to the regulation of bone remodelling and paving the way for the development of cell-free strategies for bone regeneration.
APPROVED
Keywords: miRNAs; Bone; Osteoporosis; Osteoclasts; Extracellular Vesicles